Serum 17Î²- oestradiol, progesterone and cortisol level during biological stress period of normal and sub-oestrous cycles of crossbred cattle of Asom - BONIA, k K; GOSWAMI, J (The Indian Journal of Animal Sciences, 2011)
The study was planned to compare serum 17Î²- oestradiol, progesterone and cortisol level during biological stress period of normal and sub-oestrous cycles of crossbred cattle of Asom. Jugular blood samples were collected from ten normal cyclic and ten sub-oestrous cows on day 0, 5, 10, 15 and 20 of cycles for the present study. These 3 hormones were estimated by using radioimmunoassay technique. Both 17Î²- oestradiol and progesterone concentrations in serum were varied significantly (P